Fatigue Reliability Optimization for Three-Axle Bogie Frame Based on Response Surface Method - Xinli HAN; Yuehua GAO (机车电传动)
The three-axle bogie frame was taken as the research object, the reliability analysis for structural strength and fatigue life of the key welds were carried out. Based on the thickness variables of key plates, the anti-fatigue lightweight model for the bogie frame was proposed with strength and fatigue life constraints. This optimization model was solved by the reduced response surface method. The optimization results showed that the total mass was reduced by 4.3%. This optimization result was more reasonable by consideration of uncertainties, which provided a reference for structure optimization.